(untitled) - Ivancevich, John M. (Chicago, 1994)
This book pays attention to the application of HRM approaches in "real" organizational settings and situations. Realism, understanding, and critical thinking were important in the revision. Students and faculty alike have identified readability and relevance as key strengths of the text. It provides a book that stimulates ideas and keeps all users up-to-date on HRM thinking and practice
Keywords: Personnel management,Quản trị nhân sự,Personnel management,Quản trị nhân sự; Case studies,Tình huống nghiên cứu